The Use Of Pedagogical Technologies In Teaching A Foreign Language - Ruziyeva Komila Yangiboyevna (Euro Asian Journal Publishing, 2024)
Today, a foreign language is not just a part of the culture of a certain nation, but it is also the key to success and a successful future career for students. The main learning strategy is a personality-oriented approach that puts the child's personality, abilities, inclinations and needs at the center of the educational process. All this can be implemented on the basis of new educational technologies.
Keywords: foreign language; pedagogical technology; methodology, innovation